Antibody response dynamics to the Plasmodium falciparum conserved vaccine candidate antigen, merozoite surface protein-1 C-terminal 19kD (MSP1-19kD), in Peruvians exposed to hypoendemic malaria transmission - Torres, Katherine J (BioMed Central, 2008)
BACKGROUND: In high-transmission areas, developing immunity to symptomatic Plasmodium falciparum infections requires 2–10 years of uninterrupted exposure. Delayed malaria-immunity has been attributed to difficult-to-develop and then short-lived antibody responses. METHODS: In a study area with <0.5 P. falciparum infections/person/year, antibody responses to the MSP1-19kD antigen were evaluated and associations with P. falciparum infections in children and adults. In months surrounding and during the malaria seasons of 2003–2004, 1,772 participants received ≥6 active visits in one study-year. Community-wide surveys were conducted at the beginning and end of each malaria season, and weekly active visits were completed for randomly-selected individuals each month. There were 79 P. falciparum infections with serum samples collected during and approximately one month before and after infection. Anti-MSP1-19kD IgG levels were measured by ELISA. RESULTS: The infection prevalence during February-July was similar in children (0.02–0.12 infections/person/month) and adults (0.03–0.14 infections/person/month) and was negligible in the four-month dry season. In children and adults, the seroprevalence was maintained in the beginning (children = 28.9%, adults = 61.8%) versus ending malaria-season community survey (children = 26.7%, adults = 64.6%). Despite the four-month non-transmission season, the IgG levels in Plasmodium-negative adults were similar to P. falciparum-positive adults. Although children frequently responded upon infection, the transition from a negative/low level before infection to a high level during/after infection was slower in children. Adults and children IgG-positive before infection had reduced symptoms and parasite density. CONCLUSION: Individuals in low transmission areas can rapidly develop and maintain αMSP1-19kD IgG responses for >4 months, unlike responses reported in high transmission study areas. A greater immune capacity might contribute to the frequent asymptomatic P. falciparum infections in this Peruvian population.